Perbaikan Instalasi Bangunan, Penyediaan Air Bersih, Pembuangan Limbah dan Dapur di Pondok Pesantren Latansa Murodak Tangerang - Nurhedhi Desryanto; RB Budi Kartika W; Harman Sudjanto; KGS Ismail; Rubby Soebiantoro (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2021)
The Latansa Murodak Islamic Boarding School is one of the Islamic boarding schools in Rancagong Village, Legok District, Tangerang, which organizes Islamic religious learning activities for students. This Islamic boarding school has major problems, namely a lack of clean water, no proper toilet, and no lighting. Another problem faced is the improper disposal of waste from bathrooms and kitchens. With this program, it is hoped that it will help this boarding school in learning activities more comfortably so that students can focus on gaining knowledge. The physical results of the implementation of the Indonesian Aviation Polytechnic Community Service Program are proper toilets, repair of lighting lamps, installation of pumps and water toren, and waste disposal sites.